Pemberdayaan Potensi Sosial Masyarakat Melalui Yayasan Aksi Cepat Tanggap (ACT) Bandung - Irma Nuraeni; Agus Ahmad Safei; Rohmanur Aziz (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
Humanity issue is the main things that need to be developed for the development of community welfare in the social, educational, economic and religious fields. This writing aims to find out the existence of the Aksi Cepat Tanggap Foundation (ACT) in the midst of the Bandung community in developing the potential and development of a strong civil society which has the potential to empower and develop the community. The research method used is a field study method by conducting surveys, interviews and documentation directly to the Foundation branch office. Data processing and analysis includes the process of collecting data, classifying data, connecting data with one another, analyzing data, and drawing conclusions. So it can be concluded that with the role of social capital, trust, accountability and transparency improve the condition of community welfare.